Copper- and Iron-Based Nanoflowers in Cancer Theranostics - Agathi Vlachou; Despina A. Gkika; Pavlos Efthymiopoulos; George Z. Kyzas; Alexandros Tsoupras (Applied Sciences)
In recent years, nanoscience and nanotechnology have gained prominence within materials science, offering new opportunities for cancer diagnosis and treatment. Advances in nanotechnology have allowed for the manipulation and size control of nanomaterials, leading to the development of a wide range of materials. The use of nanomaterials as chemical biology tools in cancer theranostics has been widely investigated, owing to their enhanced stability, biocompatibility, and improved cell permeability. These properties enable precise targeting while addressing the limitations of conventional cancer treatments. Nanoflowers, a specific class of nanomaterials, have recently attracted significant interest due to their promising properties for several biomedical applications. However, despite the growing attention toward nanoflowers, detailed reviews on the subject have been limited. This work focuses on two primary types of hybrid nanoflowers: iron- and copper-based ones. Within this article an overview of recent applications in cancer theranostics are thoroughly reviewed, while the synthesis processes for controlling morphology and size, underlying functions, and their characteristics and uses are also extensively explored, aiming to provide a guide for future developments in the field.